PENGEMBANGAN E-LKPD BERBANTUAN NEARPOD PADA MATERI RELASI DAN FUNGSI - Maryah, Sofa; Rustina, Ratna; Prabawati, Mega Nur (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2025)
This study aims to develop a Nearpod-assisted E-LKPD on the topic of relations and functionsthat is both valid and practical to use. The method used is Research and Development (R&D) with theADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Data collectiontechniques included unstructured interviews and questionnaires. Research instruments consisted ofinterview grids, E-LKPD quality assessment sheets, and student response questionnaires. Data wereobtained from material experts, media experts, and Grade VIII students of MTs Leuwiseeng. Data analysisinvolved calculating percentage scores from validators and questionnaires, which were then interpretedinto feasibility and practicality categories. The development process began with analysis, revealingstudents’ difficulties in understanding the concept. The design stage produced an initial draft, which wasdeveloped and validated by experts during development. Revisions were made based on expert input. Thevalidated product was tested in a small group, leading to further improvements and a second developmentphase. A broader field test was then conducted during the second implementation stage. Based onevaluation results, the final E-LKPD was considered appropriate, feasible, and practical for use.